Pengaruh Manajemen Modal Kerja dan Struktur Modal terhadap Profitabilitas Perusahaan yang Terdaftar di BEI - Anggari Ninditia, Juniar; Siska, Elmira; Indra, Natal (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
Working capital is the amount of current assets used to carry out the company's daily operations, while capital structure refers to the proportion of capital obtained from various sources, such as debt and own capital. Profitability is a measure of financial performance that shows how effectively a company generates profits from its operations. This study aims to analyze the effect of working capital (WCT) and capital structure (DER) on the level of profitability (ROA) of companies. This research method uses a quantitative approach. The data source is in the form of finances for manufacturing companies in the food and beverage sub-sector on the IDX for the 2019-2022 period. The sampling technique was porposive sampling so that 31 companies were netted. Data analysis techniques include descriptive statistical tests, classic assumption tests, multiple linear regression tests, t tests, and f tests. The results of the study show that partially WCT has a positive and significant effect on ROA. partially DER has a positive and significant effect on ROA. Simultaneously, both WCT and DER have a positive and significant effect on ROA. The practical implication of this research is that company management can use the findings of this research to optimize the management of their working capital and capital structure, so as to increase the company's profitability.